Avaliação da resposta imune de camundongos C57BL/6 imunizados com antígeno solúvel ou com as proteínas recombinantes SAG2A e BSR4 de Toxoplasma gondii formuladas em lipossomos - Vaz, Letícia Delfini (2014)
The Toxoplasma gondii is an intracellular parasite that causes toxoplasmosis and is widely prevalent in humans and other animals. In this study we investigated the immunogenicity and protective efficacy of soluble antigen of T. gondii- STAg and the recombinant proteins SAG2A and BSR4. The proteins in combination with liposomes were administered intraperitoneally in C57BL/6 mice and the antibody levels were assessed during immunizations by ELISA. Following challenge with cysts of T. gondii ME-49 strain were measured: brain inflammatory lesions, total parasitism, inflammatory score and animals survival curves. All animals immunized with recombinant proteins or STAg in combination with liposomes showed a gradual increase in levels of total IgG and IgG2a. The levels of specific IgG1 to BSR4 were significantly higher than the other immunized groups. Mice immunized with Lip-STAg showed 100 % survival, whereas immunization with Lip-BSR4 showed the least protective effect with only 60 % survival. As expected the unimmunized group (PBS only) had the highest mortality rate (44 %). The PBS group showed higher levels of cytokine production, whereas the group immunized with Lip-BSR4 got the lowest levels of cytokine. The mice immunized with SAG2A-Lip showed lower inflammatory score and statistically significant difference could not be observed among the other groups analyzed. Then concludes that STAg or SAG2A protein in combination with liposomes enhanced protection in mice, whereas immunization with liposome-BSR4 led to a decrease in immune response against the parasite T. gondii.